Neuronal Loss and Decreased GLT-1 Expression Observed in the Spinal Cord of Pembroke Welsh Corgi Dogs With Canine Degenerative Myelopathy. (May 2014) - Ogawa, M.; Uchida, K.; Yamato, O.; Inaba, M.; Uddin, M. M.; Nakayama, H.
Canine degenerative myelopathy (DM) is a progressive neurodegenerative disease that is frequently found in Pembroke Welsh Corgi (PWC) dogs. Canine DM is potentially a spontaneous animal model for human amyotrophic lateral sclerosis (ALS) because of similar lesions and the involvement of superoxide dismutase 1 (SOD1) mutation. However, the ventral horn lesion in DM has not been characterized in detail. Glutamate excitotoxicity due to deficiency of the glutamine-glutamate cycle has been implicated in neuron death in ALS. Thus, we examined 5 PWC dogs with an SOD1 mutation that were affected by DM, 5 non-DM PWC dogs, and 5 Beagle dogs without neurologic signs to assess the neuronal changes and the expression levels of 2 glial excitatory amino acid transporters (glutamate transporter 1 [GLT-1] and glutamate/aspartate transporter [GLAST]). The number of neurons in the spinal ventral horns of the DM dogs was significantly decreased, whereas no change was found in the cell size. Chromatolysis, lipofuscin-laden neurons, and marked synapse loss were also observed. GLT-1 expression was strikingly decreased in DM dogs, whereas GLAST expression showed no significant change. The results indicate that excitotoxicity related to the reduced expression of GLT-1, but not GLAST, may be involved in neuron loss in DM, as in human ALS, whereas intraneuronal events may differ between the 2 diseases.